Characteristics and Risk Factors of Out-of-Hospital Cardiac Arrest Within 72 Hours After Discharge. (October 2015) - Syue, Yuan-Jhen; Yen, Yung-Lin; Cheng, Shih-Yu; Hung, Chih-Wei; Lin, Yan-Ren; Wu, Kuan-Han
Abstract: Objective: To determine the characteristics and risk factors for patients who developed out-of-hospital cardiac arrest (OHCA) within 72 hours after emergency department (ED) discharge. Methods: A nested case-control study (1:4 ratio) was conducted in 5 EDs from January 2002 to December 2011. The study group consisted of adults experiencing nontraumatic OHCA who revisited ED within 72 hours after discharge. Patients matched in sex, age group and chief complaints were selected for the control group. Demographic data, discharge diagnosis, discharge vital signs and laboratory result were collected. Etiologies of cardiac arrest and whether the events were expected or related to the 1st ED visit were reviewed. Results: In all, 1, 657, 870 patients were discharged during the study period; 109 developed OHCA within 72 hours of ED discharge (6.6/100, 000 per year). The mean age was 64.7 years and 67.9% were men. After comparison with the control group, a higher heart rate (88.5 ± 18.23 versus 81.7 ± 15.93 beat per minutes, P = 0.003) and higher serum creatinine level (2.2 ± 2.30 versus 1.4 ± 1.38 mg/dL, P = 0.002) remain the statistical significant characteristics of study group by conditional logistic regression. Approximately 60% events were expected or unrelated to the 1st ED visit. Among patients whose OHCA were unexpected and related to the 1st ED visit, 71.4% had a cardiac cause. Of these, 20% had chest pain, but 40% had angina-equivalent symptoms during 1st presentation. Conclusions: A higher discharge heart rate and higher creatinine level are risk factors in these patients.